FORMATION OF PROFESSIONAL MOTIVATION OF FUTURE MUSIC TEACHERS FOR RESEARCH AND PROJECT ACTIVITIES (Web of Teachers: Inderscience Research, 2023)
The Innovative Development Strategy of the Republic of Uzbekistan for the period until 2020 focuses on attracting and retaining youth in the field of science and technology. The modern educational environment of higher educational institutions is aimed at developing a high degree of motivation and interest in scientific knowledge, project and research activities among university graduates [1, 3]. Forming professional motivation of students - future music teachers for research and project activities is the key to success in future professional activities, career and professional development.